2007
DOI: 10.1002/aic.11349
|View full text |Cite
|
Sign up to set email alerts
|

CFD modeling of pump‐mix action in continuous flow stirred tank

Abstract: The present work involves Computational Fluid Dynamics (CFD) modeling and validation of head and power characteristics of a Top Shrouded Turbine with Nonradial Rectangular Blades (TSTNRB) operated in backswept mode. Following the successful validation reported here and in two previous studies by the authors. CFD has been used to simulate the performance of different kinds of impellers viz. Straight Blade Paddle (SBP), Rushton Turbine (RT), Top Shrouded Turbine with Radial Rectangular Blades (TSTRRB), Top Shrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, it is hard to intuitively evince the influence of dispersed-phase viscosity on the DSDs, as there are several variables with different systems. In such a scenario, the drop diameter d was substituted with d / We –0.6 in the x coordinate to isolate the effect of the dispersed-phase viscosity, where We is the impeller Weber number, We = ρ c N 2 D 3 /σ. This conversion was based on the general conclusion that the mean drop size depends on the −0.6 power of Weber number in stirred vessels. Moreover, it is also valid for low viscous systems in this study (as shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is hard to intuitively evince the influence of dispersed-phase viscosity on the DSDs, as there are several variables with different systems. In such a scenario, the drop diameter d was substituted with d / We –0.6 in the x coordinate to isolate the effect of the dispersed-phase viscosity, where We is the impeller Weber number, We = ρ c N 2 D 3 /σ. This conversion was based on the general conclusion that the mean drop size depends on the −0.6 power of Weber number in stirred vessels. Moreover, it is also valid for low viscous systems in this study (as shown in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The computational approach adopted in the simulations involves numerical solution of the Reynolds‐averaged Navier–Stokes equations and equations of standard k–ε model of turbulence for incompressible fluid . A commercial solver FLUENT 6.3.26 is used for carrying out numerical simulations.…”
Section: Computational Approachmentioning
confidence: 99%
“…A mixer containing the pump-mix impeller is named pump-mixer. 5 During the operation, the liquid−liquid phases are aspirated into the mixer for mixing, and a well-controlled drop size distribution (DSD) is desired to enhance the hydrodynamics and masstransfer performance of the two-phase flow. Due to the inhomogeneous distribution of the turbulence intensity in space and energy dissipation rate in the mixer, the phases are often not uniformly distributed throughout the mixer.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various types of equipment were adopted in the industry, for example, centrifugal extractors, extraction columns, , and mixer-settlers . Among them, mixer-settlers are one of the most widely used ones because of their inherent advantages such as high efficiency of the stage, strong adaptability, simple operation, and large processing capacity. Generally, mixer-settlers adopted in industry have a multi-stage structure. A cascade of mixer-settlers requires inter-stage fluid transportation of two phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation